PEMBELAJARAN MENULIS TEKS EKSPLANASI DENGAN MENGGUNAKAN METODE MIND MAPPING - Rini Siti Nurjanah; Wikanengsih Wikanengsih; Yeni Rostikawati (IKIP Siliwangi, 2020)
This research was conducted to study the learning of explanatory text writing that raises various problems including, students difficulties in expressing ideas through written language, students' difficulties in starting the writing process and students difficulties in developing the right words. This research was conducted on eighth grade students of Darul Hikmah Parongpong Middle School. This study aims to describe the learning of writing explanatory texts using mind mapping methods, fostering students curiosity in writing especially in writing explanatory texts, and to overcome students difficulties in pouring ideas into thinking in writing explanatory texts. This research method uses descriptive qualitative which aims to describe naturally and systematically from the results of writing explanatory texts, as well as using data collection techniques with writing skills tests. The results of the study during the learning activities carried out on the explanatory text writing test using the mind mapping method obtained results with an average value of 19.40, with a percentage of 84.43% with good criteria. Thus learning to write explanatory texts using the mind mapping method can be said to be successful by obtaining a percentage above average.